Bilingual Education in Improving Early Childhood Communication Skills: A Systematic Literature Review - Khoiriah, Laeni Sipatu; Mirawati, Mirawati; AM, Muh. Asriadi; Halimah, Leli; Silawati, Endah (FKIP Universitas Lampung, 2025)
Abstract: Bilingual Education in Improving Early Childhood Communication Skills: Systematic Literature Review. Objectives: This study aims to comprehensively analyze bilingual education on early childhood communication skills. Methods: This research uses qualitative methods with a systematic literature review. Data was collected through electronic database literature searches namely, dimensions, eric, taylor and francis, sciencedirect and google scholar. Findings: Thirty seven articles were found that were relevant to the research topic. The results of this research show that bilingual education has great benefits for children's communication skills, especially in developing vocabulary and practicing pronunciation. Conclusion: Bilingual education is a method for improving children's communication skills, coupled with fun media and learning methods that can optimize learning and minimize the occurrence of obstacles. Keywords: children’s bilingual, communication ability, and systematic literature review.